Wild plants used as food and medicine in the Northeast of Portugal - Carvalho, Ana Maria (2011)
Resumo publicado de comunicação oral apresentada no painel Wild food plants and health in the Mediterranean area and Europe do Ninth International Congress of Ethnobiology.